Uji Aktivitas Antioksidan Fraksi N-Heksan dari Ekstrak Metanol Daun Binjai Mangifera caesia Jack. Ex. Wall Menggunakan Metode DPPH - Hafiz Ramadhan; Siti Purnama; Putri Indah Sayakti (JURNAL ILMU KEFARMASIAN INDONESIA, 2022)
Natural antioxidant compounds can be found in plants of the Mangifera genus, one of them is Mangifera caesia, Jack. ex. Wall or which was also known as binjai. This study aims to determine group compounds and the antioxidant activity of the n-hexane fraction from the binjai leaves methanol extract against 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals. The binjai leaves powder extraction was carried out using the soxhlet apparatus with methanol and liquid-liquid fractionation using water and n-hexane. Phytochemical screening was done by adding specific reagents. The antioxidant activity assay qualitatively on TLC that being sprayed with DPPH and quantitative assay by measuring the absorbance of the fraction attenuation against DPPH radicals using a UV-Vis Spectrophotometer. The Phytochemicals screening results showed that the n-hexane fraction contained phenolic, flavonoid, and steroids. The qualitative test results showed some compounds had an antioxidant activity that appeared by changing the color of the spots to yellow on a purple background after spraying with DPPH solution. The n-hexane fraction resulted in an IC50 value of 34.0668 ppm with quercetin IC50 of 2.4469 ppm. Based on these results, it can be concluded that the n-hexane fraction of binjai leaves methanol extract contains phenolic and flavonoid compounds that played a role in producing very strong antioxidant activity.